2022
DOI: 10.1021/acs.orglett.1c04219
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Addition of Prochiral Nucleophilic Alkenes to α-Chiral N-Sulfonyl Imines

Abstract: The Lewis-acid-promoted addition of prochiral E- and Z-allyl nucleophiles to chiral α-alkoxy N-tosyl imines is described. Alkene geometry is selectively transferred to the newly formed carbon–carbon bond, resulting in stereochemical control of C1, C2, and C3 of the resulting 2-alkoxy-3-N-tosyl-4-alkyl-5-hexene products. A computational analysis to elucidate the high selectivity is also presented. This methodology was employed in the synthesis of two naturally occurring isomers of clausenamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…For the ( Z) ‐crotylboronate, the Cornforth TS (ΔG ≠ =21.8 kcal/mol; Ø F,N =161.5°) also had the lowest in energy barrier, followed by the polar Felkin–Ahn transition state (ΔG ≠ =23.0 kcal/mol, Ø F,N =−65.0°). The stereochemical outcomes of our PBM crotylations are the same as those found in a recent study of the crotylation reactions of α‐chiral ‐OMe and ‐OBn N ‐sulfonyl imines with in situ generated ( E )‐ and ( Z )‐crotyl‐BF 2 species [27] . Computational analysis indicated that these reactions were also proceeding through a 6‐membered ring chair TS where addition to the imine face occurred via a Cornforth‐like conformation, [28] controlling the 1,2‐ anti configuration of the product.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…For the ( Z) ‐crotylboronate, the Cornforth TS (ΔG ≠ =21.8 kcal/mol; Ø F,N =161.5°) also had the lowest in energy barrier, followed by the polar Felkin–Ahn transition state (ΔG ≠ =23.0 kcal/mol, Ø F,N =−65.0°). The stereochemical outcomes of our PBM crotylations are the same as those found in a recent study of the crotylation reactions of α‐chiral ‐OMe and ‐OBn N ‐sulfonyl imines with in situ generated ( E )‐ and ( Z )‐crotyl‐BF 2 species [27] . Computational analysis indicated that these reactions were also proceeding through a 6‐membered ring chair TS where addition to the imine face occurred via a Cornforth‐like conformation, [28] controlling the 1,2‐ anti configuration of the product.…”
Section: Resultssupporting
confidence: 79%
“…The formation of the 1,2‐ syn ‐2,3‐ anti product 5 a can be explained by the open transition state TS‐1 involving a 5‐membered ring H‐bonded imine intermediate, with the crotyl reagent approaching the imine face anti to the Bn ring substituent to produce the 1,2‐ syn adduct (Figure 5). [27] The sterically most demanding group of the γ‐carbon of the crotyl reagent, the Me group, takes on an antiperiplanar orientation, relative to the imine moiety, to avoid unfavourable steric interactions with the 5‐membered ring methine and the N ‐Bn substituent. This places the smallest γ‐carbon substituent, the γ‐H, in a‐synclinical position over the 5‐membered ring and the double bond on the crotyl reagent in a +synclinical position, suitably oriented for the developing secondary amino group to readily capture the BPin that is generated upon cleavage of the C α ‐BPin bond.…”
Section: Resultsmentioning
confidence: 99%
“…Acylsilanes were prepared according to the literature procedure. , Potassium allyltrifluoroborate was purchased from commercial suppliers and potassium ( E )-crotyltrifluoroborate, potassium (3-methylbut-2-en-1-yl)­trifluoroborate, and potassium vinyltrifluoroborate were prepared according to the literature procedure …”
Section: Methodsmentioning
confidence: 99%
“…8g,23−25 Potassium allyltrifluoroborate was purchased from commercial suppliers and potassium (E)-crotyltrifluoroborate, potassium (3methylbut-2-en-1-yl)trifluoroborate, and potassium vinyltrifluoroborate were prepared according to the literature procedure. 26 General Procedure for Product 3. The mixture of acylsilane 1 (0.10 mmol, 1.0 equiv), potassium allyltrifluoroborate 2 (0.15 mmol, 1.5 equiv) in H 2 O (1 mL) were stirred at room temperature.…”
mentioning
confidence: 99%
“…As shown in Scheme 1b, the homolytic cleavage of an asymmetric covalent bond can provide two radical species having different nucleo-and electrophilic characteristics and hence exhibiting varying reactivity with alkenes. Alkenes are themselves generally nucleophilic 29,30 and so can selectively react with electrophilic radicals through addition to produce relatively strong nucleophilic carbon-based radicals. These radicals can then react with weak electrophilic species via radical coupling to construct additional covalent bonds.…”
Section: Introductionmentioning
confidence: 99%